Novel [1,2,4]triazolo[3,4-b][1,3,4]thiadiazine and [1,2,4]triazolo[3,4-b][1,3,4]thiadiazepine Derivatives: Synthesis, Anti-Viral In Vitro Study and Target Validation Activity - Andrey V. Khramchikhin; Mariya A. Skryl’nikova; Iana L. Esaulkova; Ekaterina O. Sinegubova; Vladimir V. Zarubaev; Maxim A. Gureev; Aleksandra M. Puzyk; Vladimir A. Ostrovskii (Molecules, 2022)
This study of the interaction system of binucleophilic 3-substituted 4-amino-4H-1,2,4-triazole-5-thiols and 3-phenyl-2-propynal made it possible to develop a new approach to synthesis of such isomeric classes as 7-benzylidene-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazine and 8-phenyl-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazepine. Among the 20 compounds studied in vitro against influenza A/Puerto Rico/8/34 (H1N1) virus, half of them demonstrated selectivity index (SI) of 10 or higher and one of them (4-((3-phenylprop-2-yn-1-yl)amino)-4H-1,2,4-triazole-3-thiol) possessed the highest (SI > 300). Docking results and values showed that the preferred interactant for our ligands was M2 proton channel of the influenza A virus. Protein-ligand interactions modeling showed that the aliphatic moiety of ligands could negatively regulate target activity level.